Agrarian Issues in the Indonesian State: Case Study of MA Decision Number 777.Pk/Pdt/2019 and Legal Protection for Landowners - Khairil Qadarisman; Fokky Fuad; Anis Rifai (Borong Newinera Publisher, 2023)
This research discusses agrarian problems that occur in Sikayah Negara Indonesia with a focus on the case study of the Supreme Court Decision Number 777.pk/Pdt/2019 and examines the legal protection given to landowners. The background to this problem comes from the agrarian conflicts that are often faced by landowners, where their ownership rights are threatened. The research method used is normative legal research with a case study approach. The collected data was analyzed qualitatively to identify emerging agrarian problems, analyze the methods used in the case studies, and evaluate the legal protection given to landowners. The results of the research show that the case study of the Supreme Court Decision Number 777.pk/Pdt/2019 involves conflicts between landowners and other parties who also claim the same land rights. The methods used include document analysis, case discussion, and legal assessment. Based on the research results, it can be concluded that legal protection for landowners in the context of agrarian problems in Sikayah Negara Indonesia is still not optimal. There are weaknesses that need to be fixed in legal policy and law enforcement to ensure better protection of land ownership rights and the interests of landowners. In order to improve this situation, further efforts are needed to improve relevant legal policies, strengthen law enforcement, and provide fair and effective protection for landowners. This will ensure the realization of balanced agrarian justice and adequate protection of the rights of landowners in the Sikayah Indonesia Country.